2004
DOI: 10.1055/s-2004-814318
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Esophagitis: a Large Retrospective Case Series

Abstract: Acute necrotizing esophagitis was more commonly recognized than has previously been reported. It is a serious clinical entity that should be considered in the differential diagnosis of upper gastrointestinal bleeding, particularly in elderly patients. The prognosis depends more on the patient's advanced age and on comorbid illnesses than on the course of the esophageal lesions, which resolved in all patients in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
121
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 7 publications
6
121
0
9
Order By: Relevance
“…AEN predominantly affects older men with comorbidities such as diabetes mellitus and cardiovascular and renal disease. Upper gastrointestinal bleeding manifesting as coffee ground vomitus and hematemesis is one of the commonest presentations and duodenal ulcer and/or duodenitis are frequently found in patients with AEN [2,17,[20][21][22]. In the present study, we found that male sex and the presence of duodenal lesions were more strongly associated with AEML than with sRE.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…AEN predominantly affects older men with comorbidities such as diabetes mellitus and cardiovascular and renal disease. Upper gastrointestinal bleeding manifesting as coffee ground vomitus and hematemesis is one of the commonest presentations and duodenal ulcer and/or duodenitis are frequently found in patients with AEN [2,17,[20][21][22]. In the present study, we found that male sex and the presence of duodenal lesions were more strongly associated with AEML than with sRE.…”
Section: Discussionsupporting
confidence: 52%
“…AEN is reportedly a rare disorder with a prevalence of 0.02-0.28% [17,21,22,24], whereas AEML including black and non-black esophagitis is presumably more common than has hitherto been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The necrosis and extensive acute inflammation frequently extend into the submucosa and even deeper into the muscularis propria, and may be associated with fibrin thrombi within dilated capillaries in the lamina propria. [4][5][6] Acute esophageal necrosis occurs in elderly patients with multiple underlying medical problems, and is thought to be caused by ischemia, as patients may also have ischemic colitis, recent surgical intervention, or hemodynamic instability. Its pathogenesis also involve gastric outlet obstruction resulting in reflux into the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenesis also involve gastric outlet obstruction resulting in reflux into the esophagus. [4][5][6] Therefore, acute mucosal necrosis shares several features with sloughing, including older patient age, comorbidities, and location in the mid and lower esophagus, but it is a much deeper and more necrotizing disease than sloughing esophagitis. Acute esophageal necrosis patients and sloughing esophagitis patients are generally older and thus both groups are more likely to have advanced atherosclerotic disease, recent preceding surgical intervention or a period of hemodynamic instability leading to ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation